2016
DOI: 10.1039/c6ra01516f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and in vitro cytotoxic activities of new steroidal thiosemicarbazones and thiadiazolines

Abstract: New steroidal thiosemicarbazones and 1,3,4-thiadiazolines as potential anticancer agents are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…Additionally, these compounds showed a strong anti-angiogenic acitivity. The results from our research also, suggest that α,β-unsaturated thiosemicarbazone moiety at C-3 as well as the spiro heterocyclic substituent at C-17 position enhanced the activity of investigated compounds [3].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Additionally, these compounds showed a strong anti-angiogenic acitivity. The results from our research also, suggest that α,β-unsaturated thiosemicarbazone moiety at C-3 as well as the spiro heterocyclic substituent at C-17 position enhanced the activity of investigated compounds [3].…”
Section: Introductionsupporting
confidence: 70%
“…3-Thiosemicarbazones and 3,17-bis(thiadiazolines) exhibited the best activity against all cancer cell lines used in this work [3]. The study of the mechanisms of anticancer activity revealed that these compounds induced apoptosis in HeLa cells, through extrinsic and intrinsic signalling pathways [3]. Additionally, these compounds showed a strong anti-angiogenic acitivity.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The next day, the extracts and cisplatin, as a positive control, were added to cells at 2IC50 concentrations. After 24 hours of incubation, the cells were stained with a mixture of acridine orange and ethidium bromide dyes (3 μg/mL acridine orange and 10 μg/mL ethidium bromide in phosphate buffered saline (PBS), and visualized under a fluorescence microscope -Carl Zeiss PALM MicroBeam with Axio Observer.Z1 using AxioCam MRm (filters Alexa 488 and 568), as already described (Matić et al, 2013a;Živković et al, 2016).…”
Section: Morphological Evaluation Of Cell Deathmentioning
confidence: 99%
“…The assay was described elsewhere (Aranda and Owen, 2009;Matić et al, 2013a;Živković et al, 2016). Plates were incubated for 2 hours.…”
Section: Tube Formation Assaymentioning
confidence: 99%